The Pilipino component of the NCEE - Ibe, Milagros D.
This study is based on performance on 159 items administered nationally in five NCEE tests. Further testing of items is needed. If Pilipino items are to be a permanent component of the NCEE, there should be a serious effort toward building up an item bank for Pilipino test questions. Further, translation of the currently used English items should be started. The National Education Testing Center should carry out continuing research on performance across regions on the Pilipino component of the NCEE, and perhaps toward gradually increasing the proportion of Pilipino items consonant to the increasing use of Pilipino with English in college courses, and to reflect a true Pilipino examination.
Keywords: Filipino language -- Examinations, questions, etc; Filipino language -- Usage; Examinations, questions, etc